Persistent and mobile organic chemicals in water resources: occurrence and removal options for water utilities. Issue 2 (29th September 2021) - Scheurer, Marco; Sandholzer, Anna; Schnabel, Tobias; Schneider-Werres, Stephanie; Schaffer, Mario; Börnick, Hilmar; Beier, Silvio
Abstract: Persistent and mobile (PM) substances are being recognized as serious threats to water resources and drinking water suppliers have to use advanced treatment if raw waters are contaminated with such compounds. In this study, analytical methods for 25 micropollutants for which insufficient or no data on their occurrence in surface waters and on their behavior during drinking water treatment were available, were developed. More than 120 surface water samples were analyzed and laboratory tests were performed to evaluate the compounds' behavior during aerobic bank filtration (BF), activated carbon treatment, and ozonation. Ensulizole, 1, 3-diphenylguanidine and 2-acrylamido-2-methylpropane sulfonic acid revealed the highest detection frequencies in the Rhine river. Concentration level and detection frequency correlated positively with the wastewater fraction. However, street run-off is likely an additional discharge pathway for 1, 3-diphenylguanidine. In simulated BF, seven (six) substances could be classified as persistent (very persistent). By applying powdered activated carbon, 42% of the substances were well removed as was the case for 50% of the compounds when applying 0.2 mg/L O3 . In total, eight of the substances detected in surface waters were weakly removed by at least one of the investigated removal processes and may cause problems for drinking water suppliers. HIGHLIGHTS: First time detections of the four anticoagulants apixaban, dabigatran, edoxaban, and rivaroxaban in surface waters on a worldwide scale. Evaluation of treatment options for waterworks to remove persistent and mobile organic chemicals. Reduction of the existing analytical gap for polar compounds. Graphical Abstract